The optimum elastica catenary cable. (December 2020) - Wang, C.Y.
Abstract: The spanning cable which has self-weight and bending stiffness is studied using the heavy elastica equations. It is found that flexural rigidity has considerable effect on the catenary properties. For a given spanning distance and rigidity, the optimum cable lengths for minimal maximum tension are determined.